Preparation and characterisation of 3D printed polyamide 6 composites for craniofacial reconstruction - Abdullah, Abdul Manaf (2020)
Craniofacial defect is typically unique and depend on the anatomical condition of the patient for which patient specific implant (PSI) is desirable. The FDM based 3D printer could be utilised to cater the needs. However, the commercially available feedstock is bio-incompatible and lack of mechanical integrity which hinder the application. This study aimed to develop a new polyamide 6 based filament feedstock aiming for craniofacial reconstruction. Polyamide 6 was compounded with carbon fibre and zinc oxide prior to filament feedstock fabrication and 3D printing processes. The effect of carbon fibre as well as hybrid carbon fibre/zinc oxide incorporation on the physicochemical properties of the compounds as well mechanical and biological properties of the 3D printed parts were assessed. The melting temperature of the composites were not affected by the filler incorporation, however, the melt flow rate, tensile, compressive and surface roughness properties of the PA 6 composites increased appreciably. The composites also exhibited better toughness properties than unfilled PA 6 after 60 days of immersion in simulated body fluid despite of high moisture absorption. The viability of osteoblast cells were more than 70% following treatment with extracted composites at concentrations of 50, 25, 12.5 and 6.25 mg/ml. The composites also demonstrated appreciable antibacterial effect against Grampositive and negative bacteria of Staphylococcus aureus and Pseudomonas aeruginosa. However, the effect was selective and more pronounced in S. aureus. The newly developed polyamide 6 based filament feedstock is compatible to be used with FDM based 3D printer. With enhanced mechanical and biological properties, the developed composites are potential to be used for craniofacial reconstruction.